'Cone dystrophy with supranormal rod response' in children. Issue 3 (6th September 2011) - Khan, Arif O; Alrashed, May; Alkuraya, Fowzan S
Abstract : Aim: To describe the initial clinical presentation of children with 'cone dystrophy with supranormal rod response, ' a distinct retinal disorder from recessive KCNV2 mutations. Methods: Retrospective case series. Results: Nine children (seven families) initially examined from 2 to 8 years of age were identified. Three had a similar initial presentation of abnormal head position with head shaking and nystagmus, while the other six presented with either infantile nystagmus (without abnormal head position or head shaking), suspected congenital glaucoma (with associated nystagmus), intermittent exotropia, V-pattern esotropia, comitant esotropia or difficulty with near vision only (reading). Only two children had clinically evident retinal changes (macular discoloration), and only two had a myopic cycloplegic refraction (the child with infantile nystagmus and the glaucoma suspect who actually had megalocornea). In addition to cone dystrophy, ERGs showed delayed scotopic responses with supranormal (six), high normal (two) or normal (one) scotopic b-wave responses to bright flash. Only one ERG (with a supranormal response) did not show a broad a-wave trough response to scotopic flash. For all patients, KCNV2 sequencing revealed one of three homozygous recessive mutations (one previously reported (p.E143X), two novel (p.Y53X, p.E80D)). The three children who presented with an abnormal head position, head shaking and nystagmus and the child who presented with infantile nystagmus had several years' follow-up, during which these findings resolved (two) or decreased (two). Conclusions: Initial clinical presentation varied, the most common presentation being abnormal head position, head shaking and nystagmus that improved with time. ERG findings are characteristic and specific for KCNV2 mutations but do not necessarily include a scotopic b-wave flash response that is supranormal under standard ERG conditions.